Adaptações neuromusculares nos músculos quadríceps e tibial anterior associadas à osteoartrite de joelho (ratos Wistar) - Cunha, Jonathan Emanuel da (2020)
Knee osteoarthritis (KOA) is one of the most disabling diseases in the world. This disease is characterized by cartilage damage, narrowing of the joint space, synovitis, osteophytes formation, joint pain and stiffness. The neuromuscular system is also very affected in KOA, however, the mechanisms of neuromuscular changes involved with this disease are poorly understood. Thus, this thesis has two main objectives: 1) Assess for changes in the neuromuscular junctions (NMJ) in rats with induced KOA anterior cruciate ligament transection (TLCA); 2) Check for KOA muscle fibrosis and correlates with muscle atrophy and inflammation. For the first study, 12 adult Wistar rats that were divided into two groups: control (without intervention, n = 6) and KOA (ALCT surgery, n = 6), after 59 days, functional tests were performed (gait test, pain, edema, knee surface temperature). In the next day the animals were euthanized, the quadriceps, tibialis anterior (TA) and gastrocnemius muscles were removed weighed and analyzed (cross sectional area of the muscle fibers, neuromuscular junction morphology, gene and protein expression), the synovial fluid was used to evaluate the total and differential leukocyte number and joint histology were also analyzed. In the second study 12 adult Wistar rats were equally divided into the control and KOA groups. 59 days after TLCA, functional tests were performed (gait test, thermal threshold and mechanical threshold), the following day the TA muscle was removed for analysis (cross-sectional area, percentage of connective tissue, gene expression and zymography). The main results found in the first study were changes in the morphology of NMJ in the quadriceps and TA, greater atrophy in TA than in the quadriceps, genetic and protein changes linked to atrophy and NMJ, in addition to changes in the gait test and functional tests. In the second study, we found muscle fibrosis in TA associated with atrophy and increased of genes expression linked to muscle inflammation. Our results in both studies help to clarify the possible mechanisms of atrophy and muscle weakness linked with KOA. We have seen that although most of the studies evaluate only the quadriceps muscle, TA muscle also seems to suffer modifications due to joint inflammation of the knee, so new studies may help to understand even better the TA remodeling mechanisms, putting on shows that it takes a broad look at the clinical treatment of this disease.